Evaluation of volatile compounds produced by Lactobacillus paracasei I90 in a hardcooked cheese model using solid phase microextraction - Peralta, Guillermo Hugo (2014)
Selected strains of mesophilic lactobacilli with key enzymatic activitiesmay be employed to intensify or diversify cheese flavor during ripening. Among enzymes of interest, aminotransferases are most important, as they are involved in the first step of amino acid (AA) catabolism. In previous studies, Lactobacillus paracasei I90 has been shown to increase both the secondary proteolysis in soft and semihard cheeses and the production of volatile compounds in minisoft cheeses. In this work, its potential for the formation of volatile compounds derived from AA catabolism was assessed by solid-phase microextraction coupled to GC-FID/MS in a hard-cooked cheese model, consisting of a cheese extract sterilized by filtration. Lb. paracasei I90 showed aminotransferase activity towards all the AAs studied (branched-chain AAs, aromatic AAs, aspartic acid, and methionine). The highest levels were observed for aspartic acid, followed by branched-chain AAs and tryptophane. Among the volatile compounds derived from AAs, 2-methylbutanal, 3-methylbutanal, diacetyl, 3-methyl1-butanol, acetic, and 3-methylbutanoic acids were detected at higher level in extracts inoculated with Lb. paracasei I90 than in controls. It was concluded that the production of volatile compounds by Lb. paracasei I90 in a hard cheese model was consistent with its main aminotransferase activities, making this strain a good candidate for enhancing flavor in hard cheeses.